2021
DOI: 10.1371/journal.pone.0246114
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency mitochondrial DNA heteroplasmy SNPs in blood, retina, and [RPE+choroid] of age-related macular degeneration subjects

Abstract: Purpose Mitochondrial (mt) DNA damage is associated with age-related macular degeneration (AMD) and other human aging diseases. This study was designed to quantify and characterize mtDNA low-frequency heteroplasmy single nucleotide polymorphisms (SNPs) of three different tissues isolated from AMD subjects using Next Generation Sequencing (NGS) technology. Methods DNA was extracted from neural retina, [RPE+choroid] and blood from three deceased age-related macular degeneration (AMD) subjects. Entire mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…As is reported by Geng et al (2019) , the heteroplasmic levels in peripheral blood leukocytes were closely associated with clinical manifestations and valuable for evaluating the clinical severity of the m.3243A>G mutation. Besides, Atilano et al (2021) found the m.13095T>C and m.13105A>G heteroplasmic levels were higher in age-related macular degeneration, with the higher heteroplasmic levels possibly representing potential biomarkers. In the present study, the association of heteroplasmic levels with KC was analyzed.…”
Section: Discussionmentioning
confidence: 88%
“…As is reported by Geng et al (2019) , the heteroplasmic levels in peripheral blood leukocytes were closely associated with clinical manifestations and valuable for evaluating the clinical severity of the m.3243A>G mutation. Besides, Atilano et al (2021) found the m.13095T>C and m.13105A>G heteroplasmic levels were higher in age-related macular degeneration, with the higher heteroplasmic levels possibly representing potential biomarkers. In the present study, the association of heteroplasmic levels with KC was analyzed.…”
Section: Discussionmentioning
confidence: 88%
“…27 Lipid hydroperoxides are created when reactive oxygen species react with polyunsaturated fatty acids such as those in drusen. 28 Of note drusen are several micro-meters away from hundreds of mitochondria in the basal RPE cell body, 29 and RPE mitochondrial DNA is damaged in AMD. 30 By contrast, SDD starts far from mitochondria of both RPE and photoreceptor inner segments at the apical RPE.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in POLG, the nuclear encoded mtDNA replicative polymerase, are also associated with familial PD, albeit likely from mtDNA depletion, providing orthogonal evidence supporting a link between mtDNA maintenance and neurodegeneration (Luoma et al, 2007). In addition to neurodegenerative diseases, increased mtDNA mutation loads have also been reported in a number of non-neurodegenerative diseases, including diabetes (Nomiyama et al, 2002), sarcopenia (Herbst et al, 2007;Shah et al, 2009), macular degeneration (Kenney et al, 2010;Atilano et al, 2021), heart disease (Matam et al, 2014), and ulcerative colitus (Baker et al, 2019), suggesting widespread, but tissue specific effects.…”
Section: Correlations Between Aging Disease and Mtdna Mutationsmentioning
confidence: 97%